The Nexus between Working Capital Management and Profitability: The Case of Listed Food and Beverage Firms in South Africa: Array - Makoni, Patricia; Ndonwabile, Mabandla (The Journal of Accounting and Management, 2020)
The purpose of this study was to assess the relationship between working capital management and profitability. It was based on a sample of 12 food and beverage firms listed on the Johannesburg Stock Exchange (JSE) in South Africa. Our study spanned 10 years from 2007 to 2016. Notwithstanding the existing literature on this relationship, very few notable studies have investigated this phenomena in this particular industrial sector. We used gross operating profit (GOP) to measure profitability, while inventory conversion period (ICP), average collection period (ACP) and average payment period (APP) were used to proxy working capital management. Applying the generalized method of moments (GMM) model, we established a negative relationship between ICP and profitability, as well as between ACP and profitability. However, we determined that there is a positive relationship between APP and profitability for our sampled firms. Based on these findings, we recommend that financial managers of such firms maintain optimal threshold levels of the various working capital components (inventory stock, accounts receivable, and accounts payable) through the adoption of an aggressive working capital management strategy to generate shareholder wealth, by enhancing the profitability of their firms.